2006
DOI: 10.1523/jneurosci.4812-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Site of Action Potential Initiation in Layer 5 Pyramidal Neurons

Abstract: Fundamental to an understanding of how neurons integrate synaptic input is the knowledge of where within a neuron this information is converted into an output signal, the action potential. Although it has been known for some time that action potential initiation occurs within the axon of neurons, the precise location has remained elusive. Here, we provide direct evidence using voltage-sensitive dyes that the site of action potential initiation in cortical layer 5 pyramidal neurons is ϳ35 m from the axon hilloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
301
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(346 citation statements)
references
References 29 publications
34
301
2
2
Order By: Relevance
“…Considering this velocity difference, we speculated that the initiation of action potentials occurs at a site less than 48 μm from the soma. This finding is consistent with the previous electrophysiological [20,21] and recent voltage-sensitive dye imaging results [39,40] in neocortical layer 5 pyramidal neurons. Using dual somatic and axonal bleb recordings in hippocampal CA3 pyramidal neurons, a recent study also revealed that, in response to somatic stimulation, action potentials are initiated in the proximal region of the axon and subsequently back-propagated into the dendrites [41] .…”
Section: Unlike Cerebellar Purkinje Cells Layer-5 Pyramidal Neuronssupporting
confidence: 93%
“…Considering this velocity difference, we speculated that the initiation of action potentials occurs at a site less than 48 μm from the soma. This finding is consistent with the previous electrophysiological [20,21] and recent voltage-sensitive dye imaging results [39,40] in neocortical layer 5 pyramidal neurons. Using dual somatic and axonal bleb recordings in hippocampal CA3 pyramidal neurons, a recent study also revealed that, in response to somatic stimulation, action potentials are initiated in the proximal region of the axon and subsequently back-propagated into the dendrites [41] .…”
Section: Unlike Cerebellar Purkinje Cells Layer-5 Pyramidal Neuronssupporting
confidence: 93%
“…The axonal initial segment (IS) is a highly specialized subdomain of the axon in which membrane proteins [such as voltage-gated sodium channels (VGNCs), potassium channels, and cell adhesion molecules] as well as cytoskeletal components (such as specialized ankyrins and spectrins) accumulate at high density (Kordeli et al, 1995;Berghs et al, 2000;Pan et al, 2006) (for review, see Salzer, 2003;Hedstrom and Rasband, 2006). As a result, the IS is a site of action potential initiation, in which neuronal firing is regulated (Coombs et al, 1957;Frankenhaeuser and Huxley, 1964;Khaliq and Raman, 2006;Palmer and Stuart, 2006;Van Wart and Matthews, 2006). Additionally, cell adhesion molecules (CAMs) clustered at the IS can serve to guide synaptogenesis during development (Ango et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Average of four and seven recordings, with each recording the result of averaging ∼40 action potentials. c to f from [41] applied voltage-sensitive dyes to map the site of action potential initiation in cortical pyramidal neurons [43], finding, in contrast to observations in cerebellar Purkinje neurons [10, but see 27], that action potential initiation occurs at the distal end of the axon initial segment. The same study also showed that once initiated, action potentials propagate down the axon in a saltatory manner.…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 70%